1998
DOI: 10.1046/j.1360-0443.1998.9368375.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cannabis use: characteristics of users in an Australian rural area

Abstract: Among long-term cannabis users in this Australian rural area, cannabis use was an integral part of everyday life and it was primarily used in social situations for the same reasons that alcohol use is used in the wider community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 2 publications
(4 reference statements)
10
131
1
6
Order By: Relevance
“…In addition, as methamphetamine can induce hallucinations and paranoia ideation (McKetin et al, 2006), it is rather surprising that amphetamine-related variables only became significantly associated with psychotic symptomatology when paranoia-related beliefs were excluded (cf research question five). In line with previous research (Reilly et al, 1998), the current study suggest that marihuana use in detained boys is particularly associated with paranoia-related psychotic experiences, while amphetamine use may be particularly related to hallucinations.…”
Section: Substance-related Variables and Psychotic Experiencessupporting
confidence: 91%
“…In addition, as methamphetamine can induce hallucinations and paranoia ideation (McKetin et al, 2006), it is rather surprising that amphetamine-related variables only became significantly associated with psychotic symptomatology when paranoia-related beliefs were excluded (cf research question five). In line with previous research (Reilly et al, 1998), the current study suggest that marihuana use in detained boys is particularly associated with paranoia-related psychotic experiences, while amphetamine use may be particularly related to hallucinations.…”
Section: Substance-related Variables and Psychotic Experiencessupporting
confidence: 91%
“…For example, D 9 -tetrahydrocannabinol (THC)-induced anxiety reactions in humans are potentiated by oral surgery procedures and during cognitive tasks accompanied by experimenter harassment (Gregg et al, 1976;Naliboff et al, 1976). Consistent with these observations, the most common reasons given for cessation of cannabis use are anxiety and panic reactions (symptoms reported in as much as 20% of subjects); however, the most common reasons given for continued cannabis use in long-term users are relaxation and reduced tension (Szuster et al, 1988;Thomas, 1996;Reilly et al, 1998). These data suggest that appropriate modulation of cannabinoid systems could have anxiolytic actions in humans.…”
Section: Introductionmentioning
confidence: 90%
“…Regular users generally prefer the more potent forms -heads of the plant 34,35 -probably because they develop tolerance to the effects of THC. 29,36 In the 1998 NDS Survey, 94% of daily and 88% of weekly cannabis users reported that they typically smoked 'heads', 'skunk' or other potent forms of cannabis.…”
Section: Changing Cannabis Marketsmentioning
confidence: 99%